PERANCANGAN APLIKASI ALKITAB ONLINE BERBASIS WEBSITE - Ronald Chandra; Wasino Wasino; Desi Arisandi (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
In this era, information systems have been increased and become more important. Computer-based information systems are widely used in various fields, one of which is in the field of spirituality, the Bible Online.Bible Online helpfully for the christians to search paragraph in bible by online. With internet they can find the contents of the bible . Here, there’s two translator, english bible and indonesian bible. Concordance are included in this bible online. Key wordsflowchart, DFD, ERD, Gantt Chart